Herpes simplex virus and early neuroimaging markers of Alzheimer's disease: Hippocampal volume and white matter integrity: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Linard, Morgane; Baillet, Marion; Letenneur, Luc; Garrigue, Isabelle; Catheline, Gwenaelle; Dartigues, Jean‐François; Pérès, Karine; Helmer, Catherine
Abstract: Background: While previous studies suggest an implication of herpes simplex virus in the onset of Alzheimer's disease (AD), no study has investigated its association with early neuroimaging markers of AD. Moreover, a genetic susceptibility factor, the APOE4 status, is suspected to intervene in the entry of the virus into neurons and could partly explain why, despite a high seroprevalence, some infected individuals remain healthy carriers, while others develop neurological consequences of the infection. The present study aims to evaluate the association between HSV status and early neuroimaging markers of AD according to APOE4 status. Method: In the AMI cohort, a population‐based prospective study on aging, the associations between HSV seroprevalence and i) hippocampal volume (n=172) and ii) white matter integrity in the parahippocampal cingulum and fornix (n=117), which are the main afferent and efferent axonal bundles of the hippocampus, were assessed according to APOE4 status. Serologies were performed at inclusion and magnetic resonance imaging scans were performed at 4 years of follow‐up. Right and left hippocampal volumes were averaged and expressed as a percentage of the total intracranial volume. White matter integrity was assessed using diffusion tensor imaging parameters: fractional anisotropy (FA) and mean diffusivity (MD). High FA and low MD values reflect a well‐organized and undamaged axon fiber architecture. Result: Among APOE4 carriers, infected subjects presented lower hippocampal volumes (p=0.04) and higher microstructural alterations of the cingulum (lower FA, p=0.04; higher MD, p<0.01) than noninfected subjects; similar nonsignificant trends were observed for the fornix. Among APOE4 noncarriers, no associations were observed. Conclusion: While the underlying mechanism remains uncertain and may involve direct action of the virus and/or the immune response against it, our findings suggest an association between HSV infection and early signs of AD among subjects with a genetic susceptibility factor, reinforcing the need to investigate the infectious hypothesis of AD and the potential related treatments.